Infant Low Birth Weight and Its Related Factors in Banyumas Regency - Setiyowati Rahardjo; Erna Kusumawati; Ibnu Zaki (Insights in Public Health Journal, 2022)
Infant Low Birth Weight (LBW) is a major factor in increased mortality and morbidity. Mother’s Factors affecting birth weight include maternal age, parity, nutritional status, disease risk, access of health care, exposure to cigarette smoke, and psychological. The number of cases of low birth weight at term deliveries at the health center II Contribute as much as 21 (41%). The number of cases of low birth weight at term birth in health centers Kedungbanteng as many as 37 (71%). This study aimed to analyze the risk factors associated with LBW in labor at term. Method Observational analytic case control study. Cases are most mothers of infants with a history BBLR in labor at term. The controls are mostly the baby's mother's closest neighbor of LBW babies who have birth about the same time but did not have a history of low birth weight. The results showed that MUAC, access to ANC, and the risk of diseases / complications linked to LBW in labor at term, and unrelated are age, parity, psychology, as well as potential exposure to smoking. LILA (OR = 4.186), disease complications (OR = 4.290) and access to ANC (OR = 2.918) are the factors that influence the occurrence of low birth weight at delivery term. Need to improve the delivery of information through extension LBW mass or individual consultation with media modules and leaflets. Keywords: Low birth weight, Upper arm circumference, disease complications